Climate change and agriculture in eastern and southern Africa: An updated assessment based on the latest global climate models - Thomas, Timothy S.; Robertson, Richard D. (International Food Policy Research Institute, 2024)
In this paper we present analysis on the recent historical trend in agriculture in the Eastern and Southern Africa (ESA) region, along with analysis of recent historical trends in temperature and precipitation. We also present 5 climate models and describe the possible future climates associated with these. We use these climate models with crop models -- for seven crops -- and bioeconomic models to further assess the impact on agricultural productivity throughout the region and how the agricultural sector will transform through 2050.